Kyrgyz Republic : Country Economic Memorandum - Enhancing the Prospects for Growth and Trade, Volume 1, Main Report - World Bank (Washington, DC, 2012)
This Country Economic Memorandum is aimed at helping the authorities in the Kyrgyz Republic identify factors explaining the apparent divergence between policies and outcomes, with a view to determining priorities for reform in the coming period. The main messages of the report are: 1) Kyrgyz policymakers should take advantage of the currently favorable nexus of a stable macro-environment, relatively strong gold production and international prices, and fast-growing neighboring markets, to address lingering policy and institutional deficiencies that limit the efficient restructuring of the economy away from its dependence on primary agriculture, mining and hydro-power. Action is needed to provide for more rapid progress with poverty reduction, and to mitigate the impact on the economy of an expected major decline in gold production by the end of the decade. Detailed quantitative analysis reveals a significant unrealized growth potential in agriculture and livestock products, agro processing and light manufacturing, based on prevailing inter-sectoral linkages in the Kyrgyz economy. 2) The prospects for successfully changing the growth pattern and trajectory, depend fundamentally on accelerated investment and export diversification. The contribution of foreign direct investments (FDI) to non-gold real sector investment has been minuscule over the past decade, limiting opportunities for much needed technology transfer and access to global value chains. The weaknesses of the export sector are reflected in the steady erosion of the Kyrgyz share of traditional regional markets. The report proposes a strategy for economic-cum-export diversification that requires simultaneous actions to address external, and domestic trade policy issues. Poor infrastructure, limited competitive pressures and low-level corruption, however, combine to raise trading costs to often prohibitively high levels. Safeguard measures remain a potential problem, and technical barriers to trade are pervasive in the CIS countries and elsewhere, although their impact on Kyrgyz exports has apparently been modest to date. Over the past few years, the government has adopted a range of measures aimed at reducing administrative barriers and strengthening the commercial legal system through a highly participatory reform process. In the end, however, it is firms not countries that are on the front line of international competition and business development. Favorable national circumstances, such as supportive macroeconomic conditions, friendly investment climates, and market-expanding trade agreements, contribute to competitiveness, but they do not guarantee success.